A Direct Method for the Efficient Synthesis of Benzylidene Acetal at Room Temperature. Issue 7 (2nd January 2019) - Reddy, Narra Rajashekar; Kumar, Rashmi; Baskaran, Sundarababu
Abstract : For the first time, a metal‐free direct method has been developed for the efficient synthesis of benzylidene acetal at room temperature using Dowex 50WX8 as a solid acid catalyst and Cl3 CCN as a novel water scavenger. At room temperature, a wide variety of aryl and α, β‐unsaturated aldehydes react readily with functionalized 1, 2‐ and 1, 3‐diols to furnish the corresponding acetals in very good yields. Labile functional groups, like N ‐Boc, N ‐Cbz, ‐OTBDMS, ‐OBn, ‐N3 and acetonide are found to be stable under the reaction conditions. The versatility of this method is further demonstrated with carbohydrate substrates and optically active diols. Abstract : A simple and direct method has been developed for the efficient synthesis of benzylidene acetal from aldehyde at room temperature. In this metal‐free method, Cl3 CCN serves as a water scavenger as well as reaction medium and the acid catalyst is readily recovered and recycled. At room temperature, a wide variety of aryl and α, β‐unsaturated aldehydes react readily with functionalized diols and optically active diols to furnish the corresponding acetals in very good yields. Several sensitive functional groups are stable under the reaction conditions.